"Meningitis‐retention syndrome": A review123. Issue 1 (5th June 2012) - Sakakibara, Ryuji; Kishi, Masahiko; Tsuyusaki, Yohei; Tateno, Akihiko; Tateno, Fuyuki; Uchiyama, Tomoyuki; Yamamoto, Tatsuya; Yamanishi, Tomonori; Yano, Masashi
Abstract Aims A peculiar combination of acute urinary retention and aseptic meningitis has been described. This combination is referred to as meningitis‐retention syndrome (MRS), since patients with this syndrome exhibited no other abnormalities, except for mild pyramidal involvement. We aimed to delineate this syndrome by reviewing literatures. Methods We performed a systematic review of the literature to identify the frequency, clinical symptoms, urodynamic findings, putrative underlying pathology, and management of this syndrome. Results Patients with MRS have typical symptoms of fever, headache, stiff neck, and minor pyramidal signs, together with acute urinary retention. The bladder is initially areflexic, but soon becomes either normal or overactive in the repeated urodynamics during the course of the disorder. MRS is thought to be a very mild form of acute disseminated encephalomyelopathy (ADEM), with increased cell count, total protein, and occasional myelin basic protein in the cerebrospinal fluid. Proper management of the acute urinary retention is necessary to avoid bladder injury due to overdistension. The effectiveness of immune treatments (e.g., steroid pulse therapy) in shortening the urinary retention period awaits further study. Conclusions Although rare, MRS is a disorder that both urologists and neurologists may encounter. MRS should be listed in the differential diagnosis of acute urinary retention. Neurourol. Urodynam. 32: 19–23, 2013. © 2012 Wiley Periodicals, Inc.